Diversity and activity pattern of ungulates in state land forest, Merapoh, Pahang - Mahamad Shubli, Nor Azmin Huda (2020)
A study of diversity and activity pattern of ungulates by using camera trap was conducted at State Land Forest, Merapoh, Pahang. The main objective of this study are to identify the diversity of ungulates and determine activity pattern of ungulates at State Land Forest. A total of 13 camera traps were used to capture the photographs of ungulates at State Land Forest. A total of four species of ungulates were detected at two location which is UMK09 and UMK11. Wild boar appeared to be the most common ungulate in the camera trap area with 213 images captured, Barking deer, Mousedeer and Malayan tapir with an images captured of 21, 57 and 5 respectively. The activity pattern of each species show Malayan tapir has nocturnal activity and mousedeer, barking deer and wild boar have diurnal activity. Further and advanced study is needed for this study research to obtain more data.